Hydroclimate of the Andes Part I: Main Climatic Features - Espinoza, Jhan Carlo; Garreaud, René; Poveda, Germán; Arias, Paola A.; Molina-Carpio, Jorge; Masiokas, Mariano; Viale, Maximiliano; Scaff, Lucia (Frontiers in Earth Science, 2020)
The Andes is the longest cordillera in the world and extends from northern South America (11°N) to the southern tip of the continent (53°S). The Andes runs through seven countries and is characterized by a wide variety of ecosystems strongly related to the contrasting climate over its eastern and western sides and along its latitudinal extension. In fact, the tropical Andes is the most biodiverse region on Earth. Currently, this region faces the highest potential impact of climate change, which could affect food security and water supplies for about 90 million people. From a scientific and societal view, the Andes present specific challenges because of its unique landscape and the fragile equilibrium between the growing population and its environment. In this manuscript, we provide an updated review of the most relevant scientific literature regarding the hydroclimate of the Andes. This review paper is presented in two parts. Part I is dedicated to summarize the scientific knowledge about the main climatic features of the Andes, with emphasis on mean large-scale atmospheric circulation, the Andes-Amazon hydroclimate interconnections, and the regular cycles of precipitation, including the most characteristic diurnal and annual cycles of precipitation. Part II, which is also included in the research topic “Connecting Mountain Hydroclimate Through the American Cordilleras”, focuses on hydroclimate variability of the Andes at a sub-continental scale.